Unusual multiscale mechanics of biomimetic nanoparticle hydrogels - Zhou, Yunlong; Damasceno, Pablo F.; Somashekar, Bagganahalli S.; Engel, Michael; Tian, Falin; Zhu, Jian; Huang, Rui; Johnson, Kyle; Mcintyre, Carl; Sun, Kai; Yang, Ming; Green, Peter F.; et al. (Nature Communications, 2018)
Viscoelastic properties are central for gels and other materials. Simultaneously, high storage and loss moduli are difficult to attain due to their contrarian requirements to chemical structure. Biomimetic inorganic nanoparticles offer a promising toolbox for multiscale engineering of gel mechanics, but a conceptual framework for their molecular, nanoscale, mesoscale, and microscale engineering as viscoelastic materials is absent. Here we show nanoparticle gels with simultaneously high storage and loss moduli from CdTe nanoparticles. Viscoelastic figure of merit reaches 1.83 MPa exceeding that of comparable gels by 100-1000 times for glutathione-stabilized nanoparticles. The gels made from the smallest nanoparticles display the highest stiffness, which was attributed to the drastic change of GSH configurations when nanoparticles decrease in size. A computational model accounting for the difference in nanoparticle interactions for variable GSH configurations describes the unusual trends of nanoparticle gel viscoelasticity. These observations are generalizable to other NP gels interconnected by supramolecular interactions and lead to materials with high-load bearing abilities and energy dissipation needed for multiple technologies.
CRIS-Team Scopus Importer:2021-12-22